EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN INKUIRI DAN PEMBELAJARAN BERBASIS MASALAH PADA MATERI POKOK BANGUN RUANG SISI DATAR DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP NEGERI DI KABUPATEN NGAWI - Ony Syaiful Rizal; Tri Atmojo Kusmayadi; Budi Usodo (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purposes of this research were to find out: (1) which one providing better mathematics learning achievement, the students with inquiry learning, problem based learning model, or direct instruction; (2) which one having better mathematics learning achievement, the students with visual, auditory, or kinesthetic learning style; (3) at each learning model, are there any difference in mathematics learning achievement between the students with visual, auditory, or kinesthetic learning style; (4) at each type of learning style, are there any difference in mathematics learning achievement between students taught using inquiry learning model, problem based learning model, or direct instruction. This study was a quasi-experimental research with a 3x3 factorial design. The hypotheses testing used two ways ANOVA with unequal cell. From the research, it could be concluded as follows. (1) The students taught with problem based learning model had better learning achievement than those taught with both inquiry learning model and direct instruction. The students taught with inquiry learning model had better learning achievement than direct instruction. (2) The learning achievement of the students with auditory learning style was better than that of those with visual and kinesthetic learning style. The learning achievement of the students with visual learning style was better than that of those with kinesthetic learning style. (3) In inquiry learning model, problem based learning model and In the direct instruction, there was no difference in learning achievement in each learning style. (4) In the students with visual learning style, the use of problem based learning model provided the better mathematics learning achievement than the use of inquiry learning model and direct instruction. The use of inquiry learning model provided the mathematics learning achievement as good as the use of direct instruction. In the students with auditory and kinesthetic learning style, there was no difference in learning achievement in each learning model.Keywords: Problem Based Learning Model, Inquiry Learning, Mathematics Learning                         Achievement